Acquisition of mechanical energy directly contributing to sideward propulsion in sidestep cutting manoeuvre - Sado, N.; Yoshioka, S.; Fukashiro, S. (Journal of Biomechanics, 2021)
Humans seldom perform steady-state forward locomotion and often change locomotive direction through non-forward propulsion. Such manoeuvrability is essential for humans; however, unsteady-locomotion mechanics are understood less than steady-state locomotion because of the difficulty in research on unsteady locomotion with a wide range of variations. Here we show the body sideward propulsion mechanism in a sidestep cutting manoeuvre. We analysed the motion and ground reaction force of 10 males during the stance phase in 90° sidestep cutting with maximal efforts and determined the segmental components to the changes in the mediolateral-kinetic (EML), anteroposterior-kinetic (EAP), and superoinferior-kinetic plus gravitational-potential energies (ESI). The medial velocity and EML increased from the beginning to the end of the stance. The stance-leg shank rotation increased EML and decreased EAP (early stance: 0.54 ± 0.17 and -1.49 ± 0.59 J/kg, late stance: 0.25 ± 0.14 and - 0.40 ± 0.17 J/kg), even while the knee and ankle work outflowed energy from the shank. The shank rotation induced over half the total increase in EML during the early stance (58 ± 7%). The stance-leg thigh rotation increased EML and decreased EAP (early stance: 0.28 ± 0.12 and -0.26 ± 0.15 J/kg, late stance: 1.43 ± 0.26 and -0.47 ± 0.13 J/kg). We added the transformation from EAP to EML by the shank and thigh rotations in the transverse plane to the sideward propulsion mechanisms, similar to the transformation from EAP into ESI in running single-leg jumps in a previous study. Coupled with previous studies, we prove the commonality in propulsion mechanisms across non-forward locomotion modes with different objective directions, which bridges the knowledge between unsteady locomotion modes.